Comparison between Celphane Taping and Skin Scrapping Method for KOH Examination In Dermatopohytosis Diagnosis - Wibowo, Antonius; Nugrahaningrum, Sulistya; Suryaningsih, Betty Ekawati; Ramadhan, Tiar; Tussqyah, Nada; Rachmawaty, Farida Juliantina (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2023)
Background: Fungal skin infections are prevalent in developing countries, with dermatophytosis and tinea versicolor being the most prevalent. The KOH test is a practical and easy-to-do examination for diagnosing superficial fungal skin infections on an outpatient basis. Skin scraping is the most known method for collecting samples for KOH testing, but some studies have shown that cellophane tape is also used for a more patient-friendly approach. Purpose: This study is aimed at comparing KOH examinations using cellophane tape and skin scrapings. Methods: This research is a diagnostic test study with a cross-sectional approach. The research data were obtained from 51 medical records of skin patients at Dr. Soedirman Kebumen Municipal Hospital with the diagnosis of tinea cruris and tinea corporis who underwent KOH examination with cellophane tape and skin scrapings. Data correlation was analyzed using the Chi square test.  Result : From the research, it was found that there was no statistically significant difference between the use of cellophane tape and skin scrapings in the KOH test sampling for tinea cases (p = 0.153), which indicates that there was no significant difference between the use of the two methods for the diagnosis of dermatophytosis. Conclusion: The tapping method as an alternative method of skin scraping for KOH examination can be used to establish the diagnosis of dermatophytosis.